2020
DOI: 10.1021/acs.inorgchem.9b02599
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Electronic Structure of High-Spin [MnIII(TPP)Cl] Using Magnetic Circular Dichroism Spectroscopy

Abstract: Manganese porphyrins are used as catalysts in the oxidation of olefins and nonactivated hydrocarbons. Key to these reactions are high-valent Mn−(di)oxo species, for which [Mn(Porph)(X)] serve as precursors. To elucidate their properties, it is crucial to understand the interaction of the Mn center with the porphyrin ligand. Our study focuses on simple high-spin [Mn III (TPP)X] (X = F, Cl, I, Br) complexes with emphasis on the spectroscopic properties of [Mn III (TPP)Cl], using variabletemperature variable-fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 78 publications
2
9
0
Order By: Relevance
“…13 Complex 1a , having low spin d 4 configuration, does not show any signal in X-band EPR in CH 2 Cl 2 solution even at 77 K. In UV-visible spectroscopy, the same solution displays a Soret band at 475 nm and Q bands at 530, 583 and 621 nm, which are typical of Mn( iii )–porphyrin complexes. 14 The crystal structure of 1a was reported earlier, which confirms that it is a five-coordinated square pyramidal complex with manganese at the center of the square plane formed by the porphyrin nitrogens and chloride as the axial ligand. 15 b…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…13 Complex 1a , having low spin d 4 configuration, does not show any signal in X-band EPR in CH 2 Cl 2 solution even at 77 K. In UV-visible spectroscopy, the same solution displays a Soret band at 475 nm and Q bands at 530, 583 and 621 nm, which are typical of Mn( iii )–porphyrin complexes. 14 The crystal structure of 1a was reported earlier, which confirms that it is a five-coordinated square pyramidal complex with manganese at the center of the square plane formed by the porphyrin nitrogens and chloride as the axial ligand. 15 b…”
Section: Resultssupporting
confidence: 71%
“…18 In a recent report from Galinato et al , it was reported that in the case of Mn( iii ) porphyrinates, the Soret band appeared around ∼475 nm. 14 Thus, the shift of the Soret band from 427 nm to 475 nm may be indicative of a one electron oxidation of complex 1 leading to the Mn( iii ) analogue.…”
Section: Resultsmentioning
confidence: 99%
“…With respect to the bond length, theoretical calculations predicted that the Mn–Cl distance would be notably larger for high-spin Mn III than for low-spin Mn III , and that the Mn–N distances would be insensitive to the Mn III spin state (Table 1). This suggests that the electronic configuration of Mn III in the high-spin state is (d yz , d zx ) 2 (d xy ) 1 (d z 2 ) 1 , as reported for porphyrin complexes, 27,28 and that in the low-spin state is (d xy ) 2 (d yz , d zx ) 2 . 19 The fact that the former possesses occupied d z 2 renders the Mn–Cl distance larger in the high-spin Mn III complex.…”
Section: Resultssupporting
confidence: 70%
“…We note that in the high-spin manganese(III) porphyrins, the normally intense Soret band splits into two less-intense bands; one of which is a prominent peak at lower energy (~470 nm), and the other one is a very broad band that occurs at higher energy (~380 nm). The ratios of bands well as the λ max values for these bands are particularly sensitive to the nature of the axial ligand(s) [ 32 , 33 ]. The X-ray structure of [(TPP)Mn III (MeTHF) 2 ]SbF 6 , as well as 1 H-NMR and IR data further support the identity of this product species as [(TPP)Mn III (MeTHF) 2 ] + (vide infra).…”
Section: Resultsmentioning
confidence: 99%